Beneficial effect of antibodies against β- secretase cleavage site of APP on Alzheimer's-like pathology in triple-transgenic mice. - Inna Rabinovich-Nikitin; Idan S Rakover; Maria Becker; Beka Solomon (PLoS ONE)
The toxicity of amyloid β and tau, the two hallmark proteins in Alzheimer's disease (AD), has been extensively studied individually. Recently new data suggest their possible interactions and synergistic effects in the disease. In this study, we investigate the ability of antibodies against the β secretase cleavage site on APP, named BBS1, to affect tau pathology, besides their well established effect on intracellular Aβ and amyloid load. For this purpose we treated the triple transgenic mice model of AD (3x Tg-AD) with mAb BBS1 intracerebroventricularly, using mini osmotic pumps for one month. The experimental data demonstrated reduction in total and phosphorylated tau levels, explained by significant reduction in GSK3β which phosphorylates tau on sites recognized by antibodies against PHF1 and AT-8. The treatment increased the cognitive capabilities and reduced the brain inflammation levels which accompany AD pathology. The data showing that tau pathology was significantly reduced by BBS1 antibodies suggest a close interaction between tau and Aβ in the development of AD, and may serve as an efficient novel immunotherapy against both hallmarks of this disease.